Recurrence of Malignant Glaucoma After Vitrectomy Intervention: A Challenging Case Series: Poster Presentation - Case Series - Resident - Maharani; Zulfa, Mazidah; P, Satya Hutama; Wildan, Arief; Rahmi, Fifin L; Puspasari, Denti (Majalah Oftalmologi Indonesia, 2023)
Introduction : Malignant glaucoma most commonly occurs after glaucoma filtration surgery. Most cases require surgical intervention such as vitrectomy. However, even after successful treatment, it can reoccur in some cases. We present two cases of recurrent malignant glaucoma. Case Illustration : The first case involved a 48-year-old female with primary angle closure glaucoma who developed malignant glaucoma 1-week after undergoing combined glaucoma surgery. The second case involved a 70-year-old man with primary angle closure glaucoma and pseudophakia who developed malignant glaucoma 4-month after trabeculectomy. They received total vitrectomy treatment. We observed anterior chamber deepening in these 2 cases, but intraocular pressure remained increased 2-week after intervention. Discussion : We found improvement in anatomy by deepening the anterior chamber, but the intraocular pressure increased in the 2 weeks. Although the problem of releasing aqueous accumulations from the vitreous has been resolved after vitrectomy, but there is no permanent passage between the anterior chamber and the vitreous cavity. So, recurrences can occur. It is possible to manage this condition by restoring aqueous flow from the anterior vitreous to the anterior chamber. YAG laser capsulo- hyaloidotomy or vitrectomy combined with hyaloido-zonula-iridectomy are frequently effective in treating underlying causes. Conclusion : Vitrectomy can help to improve the deepening anterior chamber, but intraocular pressure may remain increased after 2-week follow-up. The recurrence of malignant glaucoma may be related to incomplete resolution of the underlying condition.